The role of personality differences in achieving organisational productivity - Opare Darko, Lawrencia Irene; Bans-Akutey, Anita; Ugoh, John Kennedy; Ankomah, Harriet; Ohene Afriyie, Emelia (Annals of Management and Organization Research, 2022)
Purpose: This study examines the role of personality differences in organizational productivity. Specifically, the study examined the level of acceptance of individual differences, ascertained how individuals relate to each other to attain preset productivity levels and assessed how personality differences translate into organizational productivity. Research methodology: Using a quantitative research approach and case study design, data were collected from 190 employees through simple random sampling. Data were analyzed using descriptive statistics from IBM SPSS Statistics 24 and are presented in the tables. Results: The results showed a high level of acceptance of individual differences, even though leaders mostly failed to adjust to employee differences. It was also found that, although leaders did not invest in employee relations programs, personality differences positively affected organizational productivity. The findings also reveal that employees are creative in managing resources and materials for production, explaining the significant influence of personality differences on productivity. Limitations: The data were analyzed using descriptive statistics only. Therefore, no inferences can be made. This study was limited to the employees of the Ghana Meteorological Agency. Contribution: Organizational leaders need to become more tolerant of individual employee differences, as this goes a long way to improve organizational productivity. Future studies should consider other industries in which the workforce is more diverse. Novelty: This study highlighted the role of personality differences in achieving organizational productivity with evidence from the Ghana Meteorological Agency.